Fundamentals of Hydrogel‐Based Valves and Chemofluidic Transistors for Lab‐on‐a‐Chip Technology: A Tutorial Review. Issue 3 (21st July 2022) - Beck, Anthony; Obst, Franziska; Gruner, Denise; Voigt, Andreas; Mehner, Philipp Jan; Gruenzner, Stefan; Koerbitz, René; Shahadha, Mohammed Hadi; Kutscher, Alexander; Paschew, Georgi; Marschner, Uwe; Richter, Andreas
Abstract: Stimuli‐sensitive hydrogels have an outstanding potential for miniaturized, integrated sensor, and actuator systems and especially for lab‐on‐chip technology, but the application is still in its infancy. One major reason may be that design and realization of hydrogel‐based systems are exceptionally complex and demanding. Here, the design parameters of a key component, the hydrogel‐based valve, are discussed in their entirety. Key developments in the fields of stimuli‐sensitive hydrogels are highlighted and the necessary know‐how in material behavior, microstructuring technologies, modeling and name five essential design guidelines as well as scaling laws for hydrogel‐based components, including microfluidic one‐directional valves, microelectromechanical systems valves, self‐regulating, chemomechanical valves, and chemofluidic transistors, is provided. Abstract : Hydrogels are used as sensor‐actuator systems in many application areas and especially for lab‐on‐a‐chip technology. In this tutorial review, hydrogel‐based components for microfluidics, by highlighting the variety of stimuli‐sensitive hydrogels, basic theory in swelling kinetics, hydrogel microstructure fabrication, device simulation, scaling laws, are discussed, and finally five design rules are summarized.